2021
DOI: 10.31925/farmacia.2021.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Key Points in Fertility Preservation Treatment Strategies During Covid-19 Pandemic. An Update on Pharmacological Therapies

Abstract: The fertility preservation (FP) field has developed in the two decades and offers women the possibility to have genetic children at some point in life. Fertility preservation is urgent by definition, performed for social reasons or medical indications, such as impending gonadotoxic therapy or radical gynaecological surgery. One year after the pandemic was declared, the COVID-19 infection imposed several restrictions and limited access to health care for the infertile couple. Ovarian stimulation is a pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…During the COVID pandemic, one of the defence shields was assuring high vitamin C levels in the body [31]. For long-term ascorbic acid use, high demand for good pharmacokinetic profiles and improved gastric tolerance was welcomed [32,33]. However, in vivo, bioavailability studies and digestibility studies may be developed to perform more accurate pharmacokinetic profiles [27].…”
Section: Hesperidin Assaymentioning
confidence: 99%
“…During the COVID pandemic, one of the defence shields was assuring high vitamin C levels in the body [31]. For long-term ascorbic acid use, high demand for good pharmacokinetic profiles and improved gastric tolerance was welcomed [32,33]. However, in vivo, bioavailability studies and digestibility studies may be developed to perform more accurate pharmacokinetic profiles [27].…”
Section: Hesperidin Assaymentioning
confidence: 99%
“…The standard of care during a pandemic for male patients is sperm banking with telephone triage [ 14 ], and for female patients is simple at-home ovarian stimulation protocols before embryo/oocyte cryopreservation prior to cancer treatment [ 58 , 104 ]. Additionally, operating protocols have been modified by the cessation of laparoscopic interventions due to the risk of transmitting aerosol infection among healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…The survey tool was prepared after an extensive literature review, with similar studies published both nationally and internationally [11,12,14,15,17]. The questionnaires for this study were clustered into three parts.…”
Section: Design Of the Questionnaires And Data Collection Proceduresmentioning
confidence: 99%
“…The disease knowledge, which comprises knowledge of the causative agent, transmission and symptoms, has a significant impact on this practice [14,15]. Numerous studies document that the gap or lack of knowledge about the diseases can increase the risk of infection transmission [14,15,17]. A previous study by Yasser and Thagfan reported that 96% of Saudi adults were aware of the clinical symptoms of COVID-19 and 57.9% were correctly identified that a stuffy nose and sneezing were less common in persons infected with the virus.…”
Section: Introductionmentioning
confidence: 99%